Persistent Impairment of Testicular Histology and Sperm Motility in Adult Rats Treated with Cisplatin at Peri-Puberty - Alves Favareto, Ana Paula; Fernandez, Carla Dal Bianco; Fossato da Silva, Daniela Alessandra [UNESP]; Anselmo-Franci, Janete Aparecida; Kempinas, Wilma de Grava [UNESP] (Wiley-Blackwell, 2011)
Cisplatin is one of the most widely used and effective chemotherapeutic agents for the treatment of several human malignancies. This study evaluated the effects of peri-pubertal cisplatin administration on several reproductive end-points and the reversibility of these effects in adulthood. Peri-pubertal Wistar male rats (45 days old) were divided into two groups: control (saline 0.9%) and cisplatin (1 mg/kg/day, 5 days/week, for 3 weeks, i.p.). The study was conducted in two steps and evaluations were performed at ages of 66 (post-pubertal age) and 140 (adult age) days on: (i) organ weights, serum gonadotropins and testosterone levels, sperm counts, motility and morphology, testicular histomorphometry, spermatogenesis kinetics, Sertoli cell number and in situ detection of apoptotic germ cells and (ii) sexual behaviour, fertility and intratesticular testosterone. At the end of cisplatin therapy, rats showed reductions in sperm production and reserves, sperm with progressive movement, tubular diameter, intratesticular testosterone and fertility potential, but increased numbers of TUNEL-positive seminiferous tubules, immotile sperm and pre-implantation losses compared with control. Moreover, cisplatin-treated post-pubertal rats displayed impaired testicular histopathology and sexual behaviour. Serum gonadotropins and testosterone levels, sperm morphology, spermatogenesis kinetics and Sertoli cell number were comparable between experimental groups at both ages. Alterations found in post-puberty were recovered at adulthood, except for sperm motility and damage to testicular histology. The persistence of these cisplatin effects, despite the unaltered fertility after natural mating in rats, may have implications for reproductive function of young boys undergoing cancer therapy, given the lower reproductive efficiency in human beings compared with rats.